Socio-economic analysis of community-based micro hydro electricity schemes in Kenya - Karumba, Mary Muthoni (School of Economics, 2018)
This thesis addresses three economic and social impediments to the successful deployment of community-based micro hydro grids using a case study from the Republic of Kenya. Kenya is one of the countries in Sub-Sahara Africa currently faced with low rural electricity access rates, but with abundant micro hydro resources spread across vast rural locations. Although majority of financial resources are channeled to grid extension in developing countries like Kenya, many rural households still live 'under the grid' because they cannot afford connection fees and/or cost of grid electricity. Such phenomenon has led to innovative solutions such as the concept of Community-Based Renewable Energy Schemes (CRES), facilitating joint exploitation of a local renewable energy (RE) resources. The government of Kenya in partnership with non-state actors set up demonstration points for Community-Based Micro Hydro Schemes (CBMHS) in two locations, and other communities have adopted this model by setting up their own electrification schemes in Kenya. However, the success of such schemes continues to be very limited in Kenya and other developing countries with majority of them disintegrating after few years of operation. This phenomenon is widely documented in literature, and a variety of barriers to success of such schemes continue to be interrogated in both published and unpublished academic literature. There are issues relevant to both establishment and continued operation of such electrification that have not received much scholarly research, but continue to largely limit delivery of sustainable and quality service, as well as hindering scaling up of these potentially useful rural electrification alternatives. These include: a) mismatch between the provided services by such group electrification schemes and the expectations of their consumers b) lack of supportive capacity for joint effort mobilization and capacity for self-governance within such schemes c) unsubstantiated claims of the capability of small scale renewable energy electrification impact on households that make them not to be considered as equally important energy solutions. This thesis makes a threefold contribution to the literature of rural electrification by firstly analyzing preference for properties of decentralized electricity delivery service in a field dominated by utility provided grid solutions. Secondly, the literature on governance of man-made common pool resources (CPR) is extended by providing evidence for the requirements for successful management of a small-scale electricity commons line a CBMHS. Lastly, the study produces reliable evidence regarding immediate or short-term changes to households anticipated from small scale electrification projects. Overall, the study presents lessons on implementing and sustaining rural communities' investments in decentralized RE electrification while demonstrating why such schemes should now form essential part of rural electrification delivery models. The three research issues are addressed independently in three chapters that follow the introductory chapter of this thesis.